Women in Medicine in Nineteenth-Century American Literature : From Poisoners to Doctors, Harriet Beecher Stowe to Theda Bara /: From Poisoners to Doctors, Harriet Beecher Stowe to Theda Bara. (2018) - Crosby, Sara L
No abstract available